2021
DOI: 10.55003/cast.2022.04.22.006
|View full text |Cite
|
Sign up to set email alerts
|

Mango Seed Kernel Extract as a Natural Antioxidant in Minced Fish During Frozen Storage

Abstract: Mango seed kernel extract (MSKE) has been reported to contain high content of phenolic compounds, and exhibit strong in vitro antioxidant activity. This study aimed to evaluate the application of MSKE as natural antioxidant in frozen minced fish products. The effect of MSKE at different concentrations (0%, 1%, 2% and 3% w/w) on retarding lipid and protein oxidation in minced fish samples during frozen storage at -18 ºC was investigated and compared to the chemical antioxidant, BHT (butylated hydroxytoluene) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Similarly, Abdel-Moemin [ 33 ] also reported a decrease in sensory attributes of beef sausages during storage at lower rate in mango-seed-kernel-added products than in the control. Pinsirodom et al [ 40 ] reported that the addition of mango seed extract (6.10 at end of storage) to fish meat maintained better sensory attributes than the control (5.85 at the end of storage) due to lower lipid and protein oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Abdel-Moemin [ 33 ] also reported a decrease in sensory attributes of beef sausages during storage at lower rate in mango-seed-kernel-added products than in the control. Pinsirodom et al [ 40 ] reported that the addition of mango seed extract (6.10 at end of storage) to fish meat maintained better sensory attributes than the control (5.85 at the end of storage) due to lower lipid and protein oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Abdel-Moemin [33] also reported a decrease in sensory attributes of beef sausages during storage at lower rate in mango-seed-kernel-added products than in the control. Pinsirodom et al [40] reported that the addition of mango seed extract (6.10 at end of storage) to fish meat maintained better sensory attributes than the control (5.85 at the end of storage) due to lower lipid and protein oxidation. .09 ± 0.12 Ad 6.54 ± 0.09 Ae T0 = control (without mango seed extract), T1 = (2.5 mL/100 g of meat emulsion v/w), T2 = (5.0 mL/100 g of meat emulsion v/w) and T3 = (7.5 mL/100 g of meat emulsion v/w).…”
Section: Change In Sensory Quality Of Mango Seed Kernel Extract Incor...mentioning
confidence: 99%